Synthesis, Photophysical and Electochemical Properties of Amide-bridged Porphyrin-Anthraquinone Dimers - Liu, Li-Zeng; Liu, Dong-Zhi; Tao, Min-Li; Zhou, Xue-Qin; Li, Wei (Asian Journal of Chemistry, 2012)
Photoinduced electron-transfer processes of two newly synthesized porphyrin-anthraquinone dyads bridged with amide were studied with the UV-visible, fluorescence and transient absorption spectra. Results indicated that the intramolecular electron-transfer might take place via the excited states of the 5-(4-carboxyphenyl)-10,15,20-triphenylporphyrin unit to the anthraquinone moiety.